Pleistocene settlement in the Australian arid zone : occupation of an inland riverine landscape in the central Australian ranges - Thorley, Peter B.
Recent excavations at the Kulpi Mara Rockshelter in the Palmer River catchment of central Australia have produced radiocarbon determinations spanning an archaeological sequence of 30,000 years. These results enable re-assessment of models addressing the how, where and when of arid zone colonisation, and human adjustments to environmental change in the later Pleistocene. Whilst the evidence supports early occupation of the central arid zone during wetter conditions, doubts are raised about the continuity of occupation during the height of glacial aridity.